0389 Prevalent Insomnia Symptoms and Need for an Intervention Among Oncology Nurses. (27th May 2020) - Lee, S; Vigoureux, T F; Gonzalez, B D; Small, B J
Abstract: Introduction: Insomnia is prevalent in the working population. Nurses may be particularly vulnerable to insomnia due to demands with shift work, limited recovery between shifts, lack of control over their work, and stress associated with proximity to life-threatening health conditions. Insomnia in nurses is a significant public health burden, because it can lead to degraded quality of patient care. This study examined the prevalence of insomnia symptoms among oncology nurses and the need for an intervention to improve insomnia symptoms. Methods: Participants were 62 nurses working full-time at a cancer hospital ( M age =35.26±11.69). Participants were asked about their (1) main sleep-related complaint, (2) willingness to participate in a sleep-focused intervention, (3) preferred delivery forms of the intervention (i.e., group-based, online, and/or one-on-one), and (4) preference for content to include in the intervention (e.g., sleep hygiene education, mindfulness, cognitive-behavioral therapy). We used content analysis to analyze open-ended responses as well as descriptive statistics to summarize data. Results: Most (74%) reported difficulty falling or staying asleep or not feeling rested upon awakening as their primary or secondary sleep concerns. Nearly all nurses (95%) expressed interest in participating in a future sleep-focused intervention. In terms of preferred delivery forms of the intervention, an online intervention was most preferred (56%), followed by group meetings at the workplace (50%), and one-on-one meetings at the clinic (29%). Mindfulness strategies were preferred by most nurses (73%), followed by cognitive-behavioral therapy (48%), and sleep hygiene education (34%). Conclusion: Most oncology nurses report insomnia symptoms and the majority are interested in participating in an intervention to improve their insomnia symptoms either online or in group sessions at the workplace. The information obtained from this pilot study will serve as the basis for developing a future intervention to improve insomnia and overall sleep health in oncology nurses. Support: This work was supported, in part, by the University of South Florida College of Behavioral & Community Sciences Internal Grant Program (PI: Lee, Grant No. 0134930).